Cognitive Profiles and Functional Connectivity in First-Episode Schizophrenia Spectrum Disorders – Linking Behavioral and Neuronal Data - Rodriguez, Mabel; Zaytseva, Yuliya; Cvrčková, Aneta; Dvořaček, Boris; Dorazilová, Aneta; Jonáš, Juraj; Šustová, Petra; Voráčková, Veronika; Hájková, Marie; Kratochvílová, Zuzana; Španiel, Filip; Mohr, Pavel (Frontiers in Psychology, 2019)
The character of cognitive deficit in schizophrenia is not clear due the heterogeneity in research results. In heterogeneous conditions, the cluster solution allows the classification of individuals based on profiles. Our aim was to examine the cognitive profiles of first-episode schizophrenia spectrum disorder (FES) subjects based on cluster analysis, and to correlate these profiles with clinical variables and resting state brain connectivity, as measured with magnetic resonance imaging. A total of 67 FES subjects were assessed with a neuropsychological test battery and on clinical variables. The results of the cognitive domains were cluster analysed. In addition, functional connectivity was calculated using ROI to ROI analysis with four groups: Three groups were defined based on the cluster analysis of cognitive performance and a control group with a normal cognitive performance. The connectivity was compared between the patient clusters and controls. We found different cognitive profiles based on three clusters: Cluster 1: decline in the attention, working memory/flexibility and verbal memory domains. Cluster 2: decline in the verbal memory domain, and above average performance in the attention domain. Cluster 3: generalised and severe deficit in all of the cognitive domains. FES diagnoses were distributed amongst all of the clusters. Cluster comparisons in neural connectivity also showed differences between the groups. Cluster 1 showed both hyperconnectivity between the cerebellum and precentral gyrus, the salience network (SN) (insula cortex) and fronto-parietal network (FPN) as well as between the PreCG and SN (insula cortex) and hypoconnectivity between the default mode network (DMN) and seeds of SN (insula and supramarginal gyrus); Cluster 2 showed hyperconnectivity between the DMN and cerebellum, SN (insula) and precentral gyrus, FPN and IFG; Cluster 3 showed hypoconnectivity between the DMN and SN (insula) and SN (supramarginal gyrus) and pallidum. The cluster solution confirms the prevalence of a cognitive decline with different patterns of cognitive performance, and different levels of severity in FES. Moreover, separate behavioural cognitive subsets can be linked to patterns of brain functional connectivity.